Rancang Bangun E-Booking Klinik Kecantikan Kei Medika di Kota Jambi Berbasis Web Menggunakan Framework Codeigniter - Deika Tree Andini; M. Theo Ari Bangsa; Bastomi Baharsyah (LKP KARYA PRIMA KURSUS, 2026)
In this era of rapidly advancing technology, various aspects of life are undergoing significant transformations, including in the world of beauty services.People now prefer services that are practical, efficient, and easily accessible digitally.Kei Medika Beauty Clinic, located in Jambi City, still uses manual service booking methods through WhatsApp or by visiting the location directly.This process is considered less effective because it causes long queues, delays in service, and has the potential to reduce customer satisfaction.To address these issues, this research aims to design and build an efficient, secure, and user-friendly web-based e-booking information system to support smooth operations and improve service quality at Klinik Kei Medika.This e-booking system involves two actors: admin and user.This research uses a qualitative method with a Waterfall model system development approach consisting of five stages, namely requirement analysis, system design, implementation, testing, and maintenance.The system is developed using PHP and HTML programming languages, with a MySQL database and the CodeIgniter Framework.The system modeling tool uses Unified Modeling Language (UML) to support structured design.System testing is conducted using the Blackbox Testing method with the Equivalence Partitioning technique to test the system's functionality.In addition, User Acceptance Testing (UAT) and evaluation using the Likert Scale were also conducted.Based on the test results, the system's feasibility level is 93.14%, indicating that the system has met user needs with an interface that is easy to understand and use.It is expected that this system can help the booking process to be more structured, minimize queues, speed up service, and provide a more comfortable and satisfying experience for customers.